Learn C on the Mac - Mark, Dave (Apress, 2012)
One of the best decisions I ever made was back in 1979 when I hooked up with my buddy Tom Swartz and learned C. At first, C was just a meaningless scribble of curly brackets, semicolons, and parentheses. Fortunately for me, Tom was a C guru, and with him looking over my shoulder, I learned C quickly. Now it’s your turn. This time, I’ll be looking over your shoulder as you learn C. My goal is to present every aspect of C the way I would have liked it explained to me. I’ve saved up all the questions I had as I learned the language and tried to answer them here. Learning to program in C will open a wide range of opportunities for you. C is a tremendously popular programming language and is the basis for Java, C++, and Objective-C. Whether you want to start your own software company or just write programs for your own enjoyment, you will discover that C programming is its own reward. Most of all, C programming is fun. I hope you enjoy this book. If you have any suggestions or corrections, I’d love to hear from you. In the meantime, turn the page, and let’s get started!